Relationship between the Pavement Condition Index (PCI), Present Serviceability Index (PSI), and Surface Distress Index on Soekarno Hatta Road, Bandung - Wahyudin Nur; Bambang Sugeng Subagio; Eri Susanto Hariyadi (Institut Teknologi Bandung, 2019)
Evaluation of the conditions of Jalan Soekarno Hatta using PCI method shows that the condition of